Legendre Wavelets Method for Solving Boundary Value Problems (Journal of the College of Basic Education, 2023)
Two techniques for solving nth order boundary value problem using continuous Legendre wavelets on the interval [0, 1] are presented. The first algorithm solves the boundary value problem BVP directly use the operational matrix of derivative of Legendre wavelets while the second algorithm converts the BVP into a system of Volterra integral equations then using the operational matrix of integration for Legendre wavelets, the system of integral equations is reduced to solve a set of linear algebraic equations, some examples are presented to illustrate the ability of the algorithms.